Evaluation of Postoperative Apnea Incidence in Neonates Undergoing Minor Surgeries Under General Anaesthesia - S, Manoj; Fiona Cyril, Rosalyn; Kalam, Ashiq (Journal of Neonatal Surgery, 2025)
Background Postoperative apnea is a significant concern in neonates undergoing surgery, especially in preterm infants and those with physiological immaturity. Minor surgical procedures performed under general anaesthesia can still pose a risk of respiratory complications in this vulnerable population. Early identification of risk factors can guide postoperative monitoring strategies and improve outcomes. Aim: To evaluate the incidence and characteristics of postoperative apnea in neonates undergoing minor surgeries under general anaesthesia and identify associated perioperative risk factors. Methods A prospective observational study was conducted on 70 neonates undergoing minor elective surgeries under general anaesthesia at a tertiary care teaching hospital. Neonates were monitored postoperatively for 12 hours. Data collected included gestational age, post-conceptional age, birth weight, hemoglobin levels, surgical details, and intraoperative events. The incidence, timing, and characteristics of apnea episodes were recorded. Associations between apnea and clinical variables were analyzed using chi-square test and logistic regression. Results Postoperative apnea occurred in 12 out of 70 neonates (17.1%), most commonly within the first 6 hours after surgery. Significant risk factors associated with apnea included prematurity (p = 0.001), anemia (p = 0.009), birth weight <2.5 kg (p = 0.002), and post-conceptional age <40 weeks (p < 0.001). Most apnea episodes were mild and responded to stimulation and supplemental oxygen; only 2 cases required CPAP. Conclusion Even minor surgeries under general anaesthesia can lead to postoperative apnea in neonates, particularly those who are preterm, anemic, of low birth weight, or have a younger post-conceptional age. Routine postoperative monitoring for at least 12 hours is recommended in at-risk neonates to ensure timely intervention and improve perioperative safety.